MiR-125a-5p regulates the radiosensitivity of laryngeal squamous cell carcinoma via HK2 targeting through the DDR pathway - Wang, Qiwei; Tan, Lijun; Lv, Yuanhang; Yu, Tianjiao; Chang, Yuan; Liu, Jiangtao; Sun, Yanan (Frontiers in Oncology, 2024)
Objective: To determine the function of miR-125a-5p in laryngeal squamous cell carcinoma (LSCC), its correlation with radiation sensitivity, and the underlying regulatory mechanism.We conducted the analysis on the correlation between miR-125a-5p and head and neck squamous cell carcinoma (HNSCC) using data obtained from The Cancer Genome Atlas (TCGA). The putative gene targeted by miR-125a-5p has been identified as HK2, while the expression levels of miR-125a-5p and HK2 were measured in laryngeal cancer tissues and cells using RT-PCR. MiR-125a-5p and HK2 were introduced into the lentiviral vector and the vector was used to transfect AMC-HN-8 cells. The roles of miR-125a-5p and HK2 in LSCC and on radiosensitivity were determined by evaluating cell growth, examining colony formation, analyzing flow cytometry, and utilizing the single hit multi-target model. Western blotting was used to measure H2AX and rH2AX levels in the DNA damage response (DDR) pathway. The validation of the interaction between miR-125a-5p and HK2 was conducted through the dual-luciferase assay. To further confirm the association between miR-125a-5p and HK2, as well as its influence on radiosensitivity, rescue experiments were performed.The expression of miR-125a-5p is downregulated in LSCC, while upregulating its expression could suppress cell growth, induce apoptosis, and enhance radiosensitivity. Additionally, HK2 exhibited high expression in LSCC and the biological function was opposite to miR-125a-5p.Western blotting analysis revealed that miR-125a-5p increased rH2AX levels and decreased H2AX levels, conversely, HK2 had the opposite effect on miR-125a-5p. These findings suggested that HK2 may serve as the target gene of miR-125a-5p. The double luciferase assay confirmed the binding of HK2 to miR-125a-5p, and rescue trials confirmed the role of miR-125a-5p in regulating the effects and radiation sensitivity of LSCC by targeting HK2 via the DDR pathway.By targeting HK2 and impacting the DDR pathway, miR-125a-5p has been found to inhibit cellular proliferation, enhance apoptosis, and heighten radiosensitivity in LSCC.